Determination of ctDNA, Targeted Therapies and Immunotherapy in Non-small-cell Lung Cancer - Zhu, Chennianci; Zhuang, Weihao; Chen, Limin; Yang, Wenyu; Ou, Wen-Bin (Issues and Development in Health Research Vol. 2, 2021)
Non-small-cell lung cancer (NSCLC), a subtype of lung cancer, is one of the leading causes of cancer death in both men and women around the world. Circulating tumour DNA (ctDNA), tyrosine kinase inhibitors (TKIs), and immunotherapy have transformed our understanding of NSCLC and its treatment, from diagnosis to targeted NSCLC therapeutics. Quantifying ctDNA is convenient and precise, making clinical decisions easier. TKI-based targeted therapy and immunotherapy have also enhanced the quality of life of NSCLC patients. This article gives an update on ctDNA technologies and their implications for therapeutic options, including medications targeting the epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) with TKIs such as osimertinib and lorlatinib, the emergence of various resistance mechanisms, the control of programmed cell death-1 (PD- 1), programmed cell death ligand-1 (PD-L1), and cytotoxic T-lymphocyte antigen-4 (CTLA-4) by immune checkpoint inhibitors (ICIs) in immunotherapy and the blood tumor mutational burden (bTMB) calculated by ctDNA assay as a novel biomarker for immunotherapy. NSCLC patients, on the other hand, nevertheless confront numerous hurdles. To produce more effective medications or therapies to treat NSCLC, additional research and trials are needed.